Vibration Energy Harvesting on Vehicle Suspension Using Rotary and Linear Electromagnetic Generator - Sultoni, Arif Indro; Sutantra, I.N.; Pramono, Agus S. (IPTEK The Journal for Technology and Science, 2013)
In this paper, we discuss comparation of vehicle vibration energy harvesting between rotary and linear electromagnetic generator. We construct the two model of energy harvester mechanism and then analyze both of energy absorbtion and vehicle comfortability. Furthermore, we analyze both of energy absorbtion and vehicle comfortability. Vehicle is modeled as quarter car. Rotarty generator harvests 2.5 x 10-4 Watt. The other hand, linear generator has viscous characteristic and capable to generates 90 Watts with 12 Volt power supply for 0.03 m amplitude of bumpy road input. Linear generator reduces oscillation with 1.2 sec settling time. It is more comfort than the angular which has 3 sec in settling time. With unnevenees road input, mean power of this generator is 64 Watt.